PP1γ promotes esophageal squamous cell carcinoma progression through the PP1γ/YAP1/SOX2 axis - Du, Juan; Liu, Li; Zheng, Shutao; Dai, Chenglu; Liu, Jingyu; Zhang, Wei; Pu, Hongwei; Xue, Jing (Frontiers in Oncology, 2025)
IntroductionEsophageal squamous cell carcinoma (ESCC) is a highly aggressive malignancy with poor outcomes and limited targeted therapeutic options. While protein phosphatase 1γ (PP1γ) is overexpressed in various cancers, its role and mechanism in ESCC remains unclear. This study investigated the involvement of PP1γ in ESCC progression, particularly concerning YAP1 dephosphorylation and its regulation on stem cell markers.MethodsThe expression levels of PP1γ, YAP1, SOX2, and NANOG in ESCC tissues and adjacent non-cancerous tissue samples were analyzed using bioinformatics and immunohistochemistry. Their association with clinical features and prognosis were also analyzed. Functional assays were performed in KYSE150 cells to assess the effects of PPP1CC silencing on cell proliferation, migration, and invasion. Western blotting and qRT-PCR were used to measure the expression of YAP1, phosphorylated YAP1 (p-YAP1), SOX2, and NANOG.Results and discussionWe found that PP1γ was highly expressed in ESCC and was significantly associated with poor prognosis, lymph node metastasis, and advanced pathological stages. Patients with high PP1γ levels had significantly shorter overall survival and progression-free survival (P < 0.05). In functional assays, silencing of PPP1CC in KYSE150 cells resulted in a marked decrease in cell proliferation, as measured by CCK-8 assays (P < 0.01). Colony formation assays confirmed the reduced colony-forming ability in PPP1CC-silenced cells (P < 0.01). Furthermore, Transwell invasion and migration assays demonstrated a significant reduction in both cell migration and invasion (P < 0.01). Western blot analysis revealed that silencing PPP1CC led to an increase in p-YAP1 and the ratio of p-YAP1 to YAP1, indicating inhibited YAP1 activity, alongside significant reductions in YAP1 and SOX2 protein levels (P < 0.05), while NANOG expression remained unchanged. This change was further confirmed by the qRT-PCR. Conclusively, PP1γ may promote ESCC progression by regulating YAP1 dephosphorylation and enhancing the expression of SOX2. The PP1γ/YAP1/SOX2 axis may provide potential therapeutic targets for ESCC treatment.